Managing Emotion in Design Innovation - Singh, Amitoj (Taylor & Francis, 2014)
This book presents an emotion centered research framework titled "emoha" for design innovation. It defines emoha and underlines the importance of the developed framework in culturalization of technology and thereby design innovation. The book explains the detailed research on product styling which leads to the creation of "Emoha" and how to use it in product design.